Determinants of stock market participation - Lukas Menkhoff; Jannis Westermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
The low degree of stock market participation (SMP) is one of the big puzzles in finance. Numerous determinants have been proposed. We put these determinants into a structure that is derived from a standard static portfolio model. Then we discuss arguments put forward regarding specific SMP determinants and the empirical evidence that has been provided. The focus of our survey is on the identification of a causal impact of determinants on SMP via shocks. We summarize the evidence by suggesting established and likely SMP determinants and providing an outlook for future research and policy.
Keywords: G11; G51; 330; stock market participation; transaction costs; information; return volatility; risk tolerance